2016
DOI: 10.23937/2469-5823/1510038
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of Challenges in Engaging Urdu/Punjabi Speak People with Type 2 Diabetes in Structured Group Patient Education Using Interpretation and Established Educational Tools in Two Health Boards in Scotland

Abstract: IntroductionPeople from black and minority ethnic (BME) communities who live in upper-middle and high income countries [1] are at higher risk of type 2 diabetes than white Caucasians and they develop this at lower clinical points than white Caucasians [2,3]. A Scottish survey found that Scottish Pakistani and Indian people with type 2 diabetes were more likely to have poor diabetes control compared to white Scottish people with type 2 diabetes [4] and the Scottish Diabetes Action Plan (2010) aimed to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Undertaking digitally-enabled education at a time and a place that may be more convenient for PWD may overcome some of the known barriers to attending current educational provision such as: shame and stigma of diabetes; 22 logistics; medical or financial reasons; cultural reasons; 23 and time away from work or studies. 24,25 However, even with digital education, ongoing engagement tended to wane with time. 8,17,18,26 A systematic review and metaanalysis published in 2021 found that digital health-led DSMEs were effective in improving glucose control and diabetes knowledge.…”
Section: Digital Learning For People With Diabetesmentioning
confidence: 99%
“…Undertaking digitally-enabled education at a time and a place that may be more convenient for PWD may overcome some of the known barriers to attending current educational provision such as: shame and stigma of diabetes; 22 logistics; medical or financial reasons; cultural reasons; 23 and time away from work or studies. 24,25 However, even with digital education, ongoing engagement tended to wane with time. 8,17,18,26 A systematic review and metaanalysis published in 2021 found that digital health-led DSMEs were effective in improving glucose control and diabetes knowledge.…”
Section: Digital Learning For People With Diabetesmentioning
confidence: 99%